The Ties That Bind: Measuring the Strength of Consumers’ Emotional Attachments to Brands - Thomson, Matthew; MacInnis, Deborah J.; Whan Park, C. (Journal of Consumer Psychology, 2005)
Extant research suggests that consumers can become emotionally attached to consumption objects, including brands. However, a scale to measure the strength of consumers’ emotional attachments to brands has yet to be devised. We develop such a scale in Studies 1 and 2. Study 3 validates the scale's internal consistency and dimensional structure. Study 4 examines its convergent validity with respect to four behavioral indicators of attachments. Study 5 demonstrates discriminant validity, showing that the scale is differentiated from measures of satisfaction, involvement, and brand attitudes. That study also examines the scale's predictive validity, showing that it is positively associated with indicators of both commitment and investment. The limitations of the scale and the boundary conditions of its applicability are also discussed.